Can we playfully measure cognitive ability? Construct‐related validity and applicant reactions - Ohlms, Marie L; Melchers, Klaus G; Kanning, Uwe P (International journal of selection and assessment, 2024)
We developed a game-based assessment (GBA) measuring cognitive ability for use in personnel selection and examined its construct-related validity. Moreover, applicant reactions toward this GBA were compared with a paper-pencil-based ability test. Both assessment tools were designed to measure verbal, numerical, and figural ability. N = 183 participants completed the GBA, the paper-pencil test, and questions capturing applicant reactions and personality. We found a strong positive correlation of 0.51 between the overall GBA and paper-pencil test scores, showing evidence for its construct-related validity. Applicant reactions toward the GBA were consistently worse compared with the paper-pencil test. Furthermore, males and individuals with more video game experience held more positive perceptions than females and individuals with less video game experience.